Two new species of Schizomyia (Diptera: Cecidomyiidae) from Japan, with an updated key to larval, pupal and adult Schizomyia in Japan - Elsayed, Ayman Khamis; Yukawa, Junichi; Tokuda, Makoto (Zootaxa, 2019)
Two new species of Schizomyia Kieffer (Diptera: Cecidomyiidae: Asphondyliini: Schizomyiina) are reported from Japan. Schizomyia broussonetiae Elsayed & Tokuda n. sp. forms hairy globular leaf galls on the paper mulberry Broussonetia papyrifera (L.) Vent. (Moraceae) and S. uechiae Elsayed and Tokuda n. sp. induces red flower bud galls on the porcelain berry Ampelopsis glandulosa var. brevipedunculata (Maxim.) Momiy. (Vitaceae). Morphological features of larvae, pupae and adults of the new species are described, illustrated and compared in detail to several other Schizomyia species. An updated taxonomic key to known Japanese species of Schizomyia is provided.